Teknik untuk Mendapatkan Umpan Balik dalam Proses Pembelajaran - Muthia Khairani; Siti Rahma Nesya; Gusmaneli Gusmaneli (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
Getting quality feedback is important in many aspects of life. The teaching and learning process at school cannot be separated from the provision of teacher feedback to students. Feedback is necessary because it can provide information about students' abilities, guiding their ignorance at the time of learning something new and complex. However, in reality, not all teachers provide feedback that can motivate students' learning behavior. The method used in writing this article is the literature method by first collecting study materials and materials from various sources, namely books, journals, and related articles. The author formulates the existence of feedback techniques in the learning process, including several kinds of aids that can be received by students, so that they are easier to understand the lesson, namely visual, audio, and audio-visual aids. In addition, the role of motivation and media in the learning process for students is also very important and this can help the continuity of the teaching and learning process and the achievement of learning objectives.